ChatGPT in Education: A New Paradigm for Enhancing Student Learning and Engagement - Muhamad Basyrul Muvid; Didiet Anindita Arnandy; Achmad Arrosyidi; Sulistiowati Sulistiowati (STAI Hubbulwathan Duri, 2025)
The digitalization of education continues to evolve, with artificial intelligence (AI) playing a crucial role. ChatGPT, an AI-powered tool, has gained widespread use among students for academic purposes. This study investigates its impact on students’ learning abilities, particularly in facilitating independent learning, supporting assignment completion, and broadening knowledge. A mixed-method approach was adopted, combining quantitative survey data from 203 respondents with qualitative analysis of their responses. This methodology provided a comprehensive understanding of students' experiences and perceptions regarding ChatGPT’s role in their academic activities. The findings indicate that ChatGPT significantly aids students in completing assignments, encourages independent learning, and serves as a valuable knowledge resource. Respondents reported that ChatGPT’s accessibility and functionality contribute to enhanced learning efficiency. The study highlights ChatGPT’s potential as a transformative educational tool, emphasizing its role in digital learning environments. While students benefit from its features, considerations regarding academic integrity and critical thinking skills should be addressed. ChatGPT demonstrates considerable advantages in supporting students’ academic endeavors. Its effectiveness in fostering independent learning and knowledge expansion underscores its value in modern education. Future research should explore its long-term impact on students' learning habits and critical thinking skills.